EXCAVATION REPORT OF THE M11 TOMB OF THE SAZAGAN IN THE CITY OF SAMARKAND OF UZBEKISTAN (Scientific journal of the Fergana State University, 2023)
In 2014, 2015, 2016, the Central Asian Archaeological Group of the North-Western University, in cooperation with the Institute of Archaeological Research of the Academy of Sciences of Uzbekistan, carried out excavations in the tombs in the village of Sazagan. Different types of graves were studied at the excavation site.  In 2016, excavations were carried out in M11-2 and research was completed in M11 tombs. This report provides information on the results of the 2016 research.